PENINGKATAN KINERJA UMKM MEULIJAJAN DI CIKARANG MELALUI IMPLEMENTASI DIGITAL MARKETING - Amanda Morlian; Muhammad Fakhran al Ramadhan (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Abstract Abstract The advancement of digital technology has transformed business marketing practices, including among micro, small, and medium enterprises (MSMEs) that form the backbone of Indonesia’s economy. However, many MSMEs still rely on traditional marketing methods with limited reach. This study focuses on Meulijajan Jajan, a culinary MSME in Cikarang facing stagnant sales due to conventional promotion. The research gap lies in the lack of empirical action research assessing the direct impact of digital marketing implementation on local MSMEs. An action research method was applied, involving six participants—one business owner and five active customers. Data were collected through interviews, observations, and documentation over three months covering pre-implementation, execution, and evaluation stages. Findings indicate significant improvement in (a) sales volume (nearly doubled), (b) social media followers (+45%), and (c) market expansion to the Greater Jakarta area. The study implies that consistent brand identity, quality visual content, and interactive social engagement are essential strategies for enhancing MSME competitiveness in the digital era.